Modified NHE Distribution with Properties and Applications - Chaudhary, Arun Kumar; Sapkota, Laxmi Prasad (NUTA Journal, 2021)
We have defined a novel three-parametric model having bathtub- shaped hazard rate curve called a modified NHE distribution in this study. Several statistical features of recommended model are explicitly derived. Least square, maximum likelihood and Cramer-Von-Mises are three renowned estimations approaches which can be applied to derive model parameters. The estimators' asymptotic confidence intervals are also defined. The suggested distribution's goodness of fit is evaluated through a real data set. On real -world data set, we have discovered that the innovative suggested model outperforms other competitive models.